PENGUATAN PERSAUDARAAN DAN KERJA SAMA MAHASISWA BERBASIS NILAI SATU ARAH MELALUI MAKRAB IMKA UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - Karisma Erikson Tarigan; Rio Stepanus Tarigan (Indonesian Collaboration Journal of Community Services (ICJCS), 2026)
Through the Malam Keakraban (MAKRAB) program, which centers on the “Satu Arah” value within the Karo Students Association (IMKA) at Santo Thomas Catholic University Medan, the aim of this community service activity is to enhance brotherhood and collaboration among university students. The activity involved 45 students and took place in November 2025 at the Ojolali Natural Bathing Site in Namorambe District, Medan, North Sumatra. Lectures, group discussions, and question-and-answer sessions were the techniques employed. The results of the activity showed that participants understood the “Satu Arah” value as unity of vision and harmony of steps. They were also able to develop practical ideas for strengthening organizational connections, improving academic achievement, and preserving Karo culture. The activity concluded with a collective commitment to contribute more actively to the organization. In short, MAKRAB based on the “Satu Arah” value effectively fosters collaboration and brotherhood among IMKA students at Santo Thomas Catholic University Medan.